Martingalas en la teoría de epidemias MARTINGALAS EN LA TEORÍA DE EPIDEMIAS - Knolle Helmut (Revista Colombiana de Estadística, 2004)
A closed and homogeneously mixing population is subdivided into four classes, the susceptibles (S), the latent infected (L), the infectious (I), and the immune or removed persons (R). It is assumed that infectious persons may have contacts with any other member of the population with equal probability. Any susceptible, once contacted by an infective, becomes latent infected, then infective and at last immune or removed from the infection process. In order to get a stochastic epidemic model in discrete time it is assumed that the latent period has fixed length 1 whereas the infectious period reduces to a point. Thus, if a susceptible is infected at time t, he (she) will be infectious at time t + 1 and then removed. An epidemic model of the SIR type in discrete time is a bivariate homogeneous Markov chain (S_t; I_t) with specified transition probabilities, where S_t is the number of susceptibles and I_t is the number of infectives at time t. Once I_t = 0, no further infection can occur, i.e. the epidemic is extinct. T = mín{t : I_t = 0} is a stopping time and S_0 - S_T is the final size of the epidemic, i.e. the number of persons who became infected during the epidemic. Lefèvre & Picard (1989) have shown that a certain function of S_t; I_t and an integer-valued parameter r is a martingale, where 1 ≤ r ≤ n = S_0. Applying the optional stopping theorem, they obtain a triangular system of n linear equations from which the distribution of the final size of the epidemic can be calculated. Este artículo, de carácter divulgativo, trata del modelamiento estocástico en tiempo discreto de una epidemia en una población cerrada y homogénea. La población se divide en cuatro clases: los susceptibles (S), los infectados latentes (L), los infecciosos (I), y los inmunes o removidos (R). Un susceptible, una vez infectado por un infeccioso, será infectado latente, luego infeccioso y por fin removido del proceso de la epidemia. Para obtener un modelo en tiempo discreto se asume que el periodo latente tiene una duración constante 1 y que el periodo infeccioso se reduce a un punto. Así, un susceptible que se infecta en el instante t, será infeccioso en t + 1 y después removido. Entonces se define una cadena de Markov bivariada homogénea (S_t; I_t), donde S_t es el número de susceptibles e I_t es el número de infecciosos en el tiempo t. Si una vez I_t = 0, no ocurren más infecciones, o sea la epidemia se acaba. El tamaño final de la epidemia es S_0-S_T, donde T = mín{t : I_t = 0}. Como Lefèvre & Picard (1989) demostraron, se puede asociar a la cadena de Markov (S_t; I_t) una familia de martingalas, y el teorema de parada opcional facilita el cálculo de la distribución del tamaño final de la epidemia.